Nanorod-shaped ZSM-48 molecular sieve, preparation method thereof, hydroisomerization catalyst and application of hydroisomerization catalyst
By performing two-stage crystallization reaction at a specific temperature, nanorod-shaped ZSM-48 molecular sieve with adjustable silicon-aluminum ratio was prepared, which solved the problems of long synthesis cycle and poor hydroisomerization performance of ZSM-48 molecular sieve in the prior art, and achieved efficient hydroisomerization performance and isomeralkane selectivity.
Patent Information
- Application Number
- CN202411744249.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing synthesis method of ZSM-48 molecular sieve cannot meet the requirements of hydrogen isomerization reaction for low-silicon aluminum ZSM-48, and the synthesis period is long, resulting in poor effect in alkane hydroisomerization applications.
A nanorod-shaped ZSM-48 molecular sieve was synthesized by performing two-stage crystallization reactions at a specific temperature to obtain nanorod-shaped ZSM-48 molecular sieve with adjustable silicon-aluminum ratios, and a catalyst with high efficiency hydroisomerization performance was obtained through post-treatment.
The synthesis of nanorod-shaped ZSM-48 molecular sieve with adjustable silicon-aluminum ratio was achieved, which shortened the synthesis cycle, reduced the raw material cost, and significantly improved the hydroisomerization performance and isomerial alkane selectivity.
Smart Images

Figure CN119750607A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of molecular sieve preparation, and in particular to a nanorod-shaped ZSM-48 molecular sieve and a preparation method thereof, a hydrogenation isomerization catalyst and applications thereof. Background Art
[0002] ZSM-48 is an impurity phase first discovered during the synthesis of ZSM-39. ZSM-48 has a ferrite-based framework with non-interconnected linear one-dimensional ten-membered ring channels with a size of It is close to the kinetic diameter of normal alkanes and monobranched isoalkanes, so its unique framework structure and its alkane hydroisomerization performance have attracted widespread attention.
[0003] Current research on ZSM-48 molecular sieves is mainly focused on zeolite synthesis. For example, low Si / Al ZSM-48 is difficult to synthesize, the template agent is expensive, and the synthesis cycle is long. However, less attention has been paid to the structural advantages of ZSM-48 molecular sieves and the matching relationship between their Si / Al and catalytic performance.
[0004] ZSM-48 is a high silicon molecular sieve, and its application as an acidic carrier is limited due to its high Si / Al ratio (75). Based on this, US7482300 discloses a method for synthesizing a low silicon-aluminum ratio ZSM-48 (Si / Al<55) assisted by a seed (about 4% seed dosage), but the template used in the method is hexamethylammonium chloride, which is not only expensive but also very toxic. CN102910642A discloses a method for preparing a ZSM-48 molecular sieve, which adds three templates (templates are dibromohexane (DBH), trimethylamine (TMA) and ethanolamine (ETA)) in a certain proportion, and appropriately adjusts the dosage of the reaction mixture to successfully synthesize a ZSM-48 molecular sieve. This synthesis method greatly reduces the cost of the catalyst, but the silicon-aluminum ratio of ZSM-48 is relatively high (Si / Al>75).
[0005] Theory and practice show that the long-chain alkane hydroisomerization reaction occurs at the orifice of the one-dimensional pore ten-membered ring zeolite, so the orifice acid center accessibility is an important factor affecting the catalytic performance of the molecular sieve. CN111013643B discloses a nano ZSM-22 zeolite loaded with phosphorus nickel hydroisomerization catalyst, which is applied to the n-dodecane hydroisomerization reaction, showing high activity and isoparaffin selectivity. However, the currently synthesized ZSM-48 molecular sieves are mostly dispersed or aggregated long needle-shaped crystals, and the orifice acid center accounts for a low proportion. Therefore, the study of the synthesis and application of nano ZSM-48 molecular sieves has aroused the interest of scientific researchers.
[0006] The existing ZSM-48 molecular sieve synthesis method cannot meet the requirements of low silicon-aluminum ZSM-48 for hydroisomerization reaction and the required crystallization time is long. Therefore, the weak acidity of high silicon-aluminum ratio ZSM-48 molecular sieve limits its application in alkane hydroisomerization. The development of stable and efficient low silicon-aluminum ratio ZSM-48 molecular sieve synthesis technology and the comparison of the structural advantages of ZSM-48 molecular sieve and the relationship between Si / Al and catalytic performance are urgent issues to be solved for its large-scale industrial application. Summary of the invention
[0007] The main purpose of the present invention is to provide a nanorod-shaped ZSM-48 molecular sieve and a preparation method thereof, a hydroisomerization catalyst and its application, so as to solve the problems of high preparation cost of ZSM-48 molecular sieve in the prior art or poor effect on the hydroisomerization reaction of alkanes.
[0008] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for synthesizing a nanorod-shaped ZSM-48 molecular sieve is provided, and the method comprises: step S1, after uniformly mixing an alkali source, a template, an aluminum source, water and a silicon source, adding seed crystals for aging to obtain a gel; the molar ratio of the hydroxide in the alkali source to the silicon element in the silicon source is (0.01-0.09): 1; step S2, subjecting the gel to a first-stage crystallization at 90-110° C. to obtain a first-stage crystallization product; step S3, subjecting the first-stage product to a second-stage crystallization at 160-190° C., and subjecting the second-stage crystallization product to post-treatment to obtain a nanorod-shaped ZSM-48 molecular sieve.
[0009] Further, the alkali source is one or more of potassium hydroxide, sodium hydroxide and ammonia water;
[0010] The template agent is any one or more of pentamethamine bromide, hexamethamine bromide, hexamethamine hydroxide and 1,6-hexanediamine;
[0011] The aluminum source is any one or more of pseudo-boehmite, sodium aluminate, and aluminum sulfate;
[0012] The silicon source is any one or more of macroporous silica gel, silica gel or fumed silica;
[0013] The seed crystal is a ZSM-48 molecular sieve. Preferably, the absolute value of the difference between the silicon-aluminum ratio of the ZSM-48 molecular sieve used as the seed crystal and the silicon-aluminum ratio of the feed is within 10%.
[0014] Further, the molar ratio of silicon in the silicon source to aluminum in the aluminum source is (25-250):1, preferably (30-140):1;
[0015] The molar ratio of the template to the silicon element in the silicon source is (0.005-1.5):1, preferably (0.005-1.5):1;
[0016] The molar amount of water and the molar amount of silicon in the silicon source are (10-40):1, preferably (15-30):1;
[0017] The amount of seed crystal added is 1% to 6% of the mass of SiO2 in the silicon source.
[0018] Further, step S1 comprises: adding an alkali source, a template agent, and an aluminum source into deionized water, stirring until uniformly mixed to obtain a mixed solution, uniformly mixing a silicon source with the mixed solution, adding seed crystals for aging, and obtaining a gel;
[0019] Preferably, the stirring speed is 300-600RPM.
[0020] Furthermore, the aging time is 0.5 to 3 hours, and the aging temperature is 20° C. to 35° C.
[0021] Further, the first stage crystallization and the second stage crystallization are carried out under stirring conditions, and preferably, the stirring speeds of the first stage crystallization and the second stage crystallization are independently 30 to 50 RPM;
[0022] The crystallization period is 6 to 24 hours;
[0023] The second stage crystallization time is 12 to 24 hours.
[0024] Further, post-treatment includes washing, drying and roasting;
[0025] Washing includes washing the second-stage crystallization product with deionized water until the pH of the eluent is 7-8;
[0026] The drying temperature is 60-120°C and the drying time is 8-12h;
[0027] Calcination includes heating to 550-600°C at a rate of 2-4°C / min and maintaining for 6-12h;
[0028] The post-treatment further comprises: performing ion exchange on the calcined product in a 0.5-2 mol / L ammonium chloride solution.
[0029] According to another aspect of the present application, a nanorod-shaped ZSM-48 molecular sieve is provided. The nanorod-shaped ZSM-48 molecular sieve is prepared by any of the above-mentioned synthesis methods of the nanorod-shaped ZSM-48 molecular sieve.
[0030] According to another aspect of the present application, a hydroisomerization catalyst is provided, comprising a carrier and a metal active component, wherein the carrier is the above-mentioned nanorod-shaped ZSM-48 molecular sieve, and the metal active component comprises any one or more of Ni, Pt and Pd;
[0031] Preferably, the weight of the metal active component is 0.05-1 wt % of the weight of the carrier.
[0032] According to another aspect of the present application, there is provided a use of the above-mentioned hydroisomerization catalyst in an alkane hydroisomerization reaction;
[0033] Preferably, the temperature of the alkane hydroisomerization reaction is 240-360°C; the reaction pressure is 1-6 MPa; the volume ratio of hydrogen to alkane is 300-600; the mass space velocity is 0.5-12 h -1 .
[0034] By applying the technical solution of the present invention, a nanorod-shaped ZSM-48 molecular sieve with a large adjustable range of silicon-aluminum ratio is prepared through a two-stage crystallization reaction performed at a specific temperature, and the particle morphology is uniform and the crystallinity is high. In addition, the synthesis cycle of the synthesis method of the present application is significantly shortened, and the raw materials are cheap and easy to obtain. Compared with other one-dimensional pore zeolites, the nanorod-shaped ZSM-48 molecular sieve prepared in the present application exhibits more effective hydroisomerization performance, and the selectivity of isoparaffins is significantly improved, and it has a high application value and prospect in the field of hydroisomerization dewaxing. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0036] Figure 1 An XRD pattern of Example 1 according to the present invention is shown.
[0037] Figure 2 A SEM image of Example 1 according to the present invention is shown.
[0038] Figure 3 An XRD pattern of Example 2 according to the present invention is shown.
[0039] Figure 4 A SEM image of Example 2 according to the present invention is shown.
[0040] Figure 5 An XRD pattern of Example 3 according to the present invention is shown.
[0041] Figure 6 A SEM image of Example 3 according to the present invention is shown.
[0042] Figure 7 An XRD pattern of Example 4 according to the present invention is shown.
[0043] Figure 8 A SEM image of Example 4 according to the present invention is shown.
[0044] Fig. 9 An XRD pattern of Example 5 according to the present invention is shown.
[0045] Fig.10 An XRD pattern of Example 6 according to the present invention is shown.
[0046] Fig.11 An XRD pattern of Comparative Example 1 according to the present invention is shown.
[0047] Fig.12 A SEM picture of Comparative Example 1 according to the present invention is shown.
[0048] Fig.13 An XRD pattern of Comparative Example 2 according to the present invention is shown.
[0049] Fig.14 A SEM picture of Comparative Example 2 according to the present invention is shown.
[0050] Fig.15 An XRD pattern of Comparative Example 3 according to the present invention is shown.
[0051] Fig.16 A SEM picture of Comparative Example 3 according to the present invention is shown. DETAILED DESCRIPTION
[0052] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0053] As analyzed in the background technology of this application, the prior art has the problem that the preparation cost of ZSM-48 molecular sieve is high or the effect of hydroisomerization reaction of alkanes is poor. In order to solve this problem, this application provides a nanorod-shaped ZSM-48 molecular sieve and its preparation method, hydroisomerization catalyst and its application.
[0054] According to a typical embodiment of the present application, a method for synthesizing a nanorod-shaped ZSM-48 molecular sieve is provided, and the method comprises: step S1, after uniformly mixing an alkali source, a template, an aluminum source, water and a silicon source, adding seed crystals for aging to obtain a gel, wherein the molar ratio of the hydroxide in the alkali source to the silicon element in the silicon source is (0.01-0.09):1; step S2, subjecting the gel to a first-stage crystallization at 90-110°C to obtain a first-stage crystallization product; step S3, subjecting the first-stage product to a second-stage crystallization at 160-190°C, and subjecting the second-stage crystallization product to post-treatment to obtain a nanorod-shaped ZSM-48 molecular sieve.
[0055] The present application prepares a nanorod-shaped ZSM-48 molecular sieve with a large adjustable range of silicon-aluminum ratio through a two-stage crystallization reaction at a specific temperature. The particle morphology is uniform and the crystallinity is high. The synthesis cycle of the synthesis method of the present application is significantly shortened, and the raw materials are cheap and easy to obtain. Compared with other one-dimensional pore zeolites, the nanorod-shaped ZSM-48 molecular sieve prepared in the present application exhibits more effective hydroisomerization performance, and the selectivity of isoparaffins is significantly improved, and it has a high application value and prospect in the field of hydroisomerization dewaxing.
[0056] The above-mentioned alkali source can be selected from the prior art. In some embodiments of the present application, the above-mentioned alkali source is one or more of potassium hydroxide, sodium hydroxide and ammonia water.
[0057] In some embodiments of the present application, the template is any one or more of pentamethylammonium bromide, hexamethylammonium bromide, hexamethylammonium hydroxide and 1,6-hexanediamine; in some embodiments of the present application, the aluminum source is any one or more of pseudo-boehmite, sodium aluminate and aluminum sulfate; in some embodiments of the present application, the silicon source is any one or more of macroporous silica gel, silica gel or fumed silica;
[0058] In some embodiments of the present application, the molar ratio of silicon in the silicon source to aluminum in the aluminum source is (25-250): 1, preferably (30-140): 1. Preferably, the molar ratio of the template to the silicon in the silicon source is (0.005-1.5): 1, more preferably (0.005-1.5): 1. Preferably, the molar amount of water to the molar amount of silicon in the silicon source is (10-40): 1, more preferably (15-30): 1.
[0059] In some embodiments of the present application, the composition of each component in the mixture system formed by the alkali source, the template, the aluminum source, the water and the silicon source satisfies the following relationship in terms of molar amount: SiO2 / Al2O3=50-500, OH - / SiO2=0.005-1, HMB / SiO2=0.005-1.5, H2O / SiO2=10-40, wherein HMB represents the template. Preferably, the molar ratio of each component in the above mixture system is preferably in the range of SiO2 / Al2O3=60-280, OH - / SiO2=0.01-1, T / SiO2=0.005-1.5, H2O / SiO2=15-30.
[0060] In some preferred embodiments of the present application, the above step S1 includes: adding an alkali source, a template, and an aluminum source to deionized water, stirring until mixed evenly to obtain a mixed solution, mixing the silicon source with the mixed solution evenly, adding seed crystals for aging, and obtaining a gel; preferably, the stirring speed is 300 to 600 RPM.
[0061] In some embodiments of the present application, the seed is a ZSM-48 molecular sieve. Preferably, the amount of the seed used is 1% to 6% of the mass of SiO2 in the silicon source, and more preferably 2%. Preferably, the absolute value of the difference between the silicon-aluminum ratio of the ZSM-48 molecular sieve used as the seed and the silicon-aluminum ratio of the feed is within 10%, that is, the absolute value of the difference between the silicon-aluminum ratio of the ZSM-48 molecular sieve used as the seed and the silicon-aluminum ratio of the feed is within 10% of the silicon-aluminum ratio of the feed, specifically, the silicon-aluminum ratio of the ZSM-48 molecular sieve used as the seed and the silicon-aluminum ratio of the feed can be equal, or the absolute value of the difference between the silicon-aluminum ratio of the ZSM-48 molecular sieve used as the seed and the silicon-aluminum ratio of the feed is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. of the silicon-aluminum ratio of the feed.
[0062] After adding the seed crystal, an aging treatment is performed. In some embodiments of the present application, the aging time is 0.5 to 3 hours, and the aging temperature is 20°C to 35°C. In the preparation method of the present application, aging is performed at room temperature, which is not only convenient for implementation, but also coordinated with subsequent crystallization and other treatment conditions, so that the generated nanorod-shaped ZSM-48 molecular sieve has a better catalytic effect on the alkane hydrogenation isomerization reaction. Preferably, the aging is performed under stirring conditions, and preferably, the stirring speed is 500 to 600RPM.
[0063] In some embodiments of the present application, the first-stage crystallization and the second-stage crystallization are carried out under stirring. Preferably, the stirring speed of the first-stage crystallization and the second-stage crystallization is independently 30 to 50 RPM. Preferably, the time of the first-stage crystallization is 6 to 24 hours; the time of the second-stage crystallization is 12 to 24 hours. In some embodiments of the present application, the first-stage crystallization and the second-stage crystallization are carried out in a stainless steel synthesis kettle containing a polytetrafluoroethylene lining placed in a rotary oven.
[0064] In some typical embodiments of the present application, the post-treatment includes washing, drying and calcination to obtain nanorod-shaped ZSM-48 molecular sieve.
[0065] Specifically, the above-mentioned second-stage crystallization product can be filtered or centrifuged to obtain a solid product, and the solid product is washed with deionized water until the pH of the eluent is 7-8, for example, the pH of the eluent is 7, 7.2, 7.4, 7.5, 7.7, 7.9, etc.
[0066] In some embodiments of the present application, the drying temperature in the post-treatment process is 60-120° C. and the drying time is 8-12 h.
[0067] The dried product is calcined to remove the template in the product. In some embodiments of the present application, the calcination includes heating to 550-600° C. at a rate of 2-4° C. / min and maintaining for 6 to 12 hours.
[0068] In some embodiments of the present application, the post-treatment further includes: performing ion exchange on the calcined product in a 0.5-2 mol / L ammonium chloride solution to remove the cations (Na + or K + ) is replaced by hydrogen ions (H + ), thereby changing its acidity, directly affecting the catalytic performance and adsorption performance of the molecular sieve. For example, the temperature of the above-mentioned ion exchange is 70-90°C, and the time is 2-4h. Preferably, the above-mentioned ion exchange is exchanged at 80°C for 3h. The product slurry after the ion exchange is filtered or centrifuged to obtain a solid product. Preferably, the solid product is then dried and calcined, and the conditions for drying and calcining can refer to the above introduction. In some embodiments of the present application, the above-mentioned sample ion exchange operation is repeated until the mass content of the Na element is less than 1%, and the target product is finally obtained.
[0069] According to another typical embodiment of the present application, a nanorod-shaped ZSM-48 molecular sieve is provided, characterized in that it is prepared by the synthesis method of the nanorod-shaped ZSM-48 molecular sieve according to any one of claims 1 to 7.
[0070] The above preparation method prepares a nanorod-shaped ZSM-48 molecular sieve with a large adjustable range of silicon-aluminum ratio through a two-stage crystallization reaction at a specific temperature, and the particle morphology is uniform and the crystallinity is high. In addition, the synthesis cycle of the synthesis method of the present application is significantly shortened, and the raw materials are cheap and easy to obtain. Compared with other one-dimensional pore zeolites, the nanorod-shaped ZSM-48 molecular sieve prepared in the present application exhibits more effective hydroisomerization performance, and the selectivity of isoparaffins is significantly improved, and it has a high application value and prospect in the field of hydroisomerization dewaxing.
[0071] According to another typical embodiment of the present application, a hydroisomerization catalyst is provided, which includes a carrier and a metal active component, wherein the carrier is the above-mentioned nanorod-shaped ZSM-48 molecular sieve, and the metal active component includes any one or more of Ni, Pt and Pd. Since the nanorod-shaped ZSM-48 molecular sieve prepared in the present application exhibits more effective hydroisomerization performance, the hydrogenation catalyst loaded with the active metal component has significantly improved selectivity for isoparaffins, and has high application value and prospects in the field of hydroisomerization dewaxing.
[0072] In some preferred embodiments, the weight of the metal active component is 0.05-1wt% of the weight of the carrier, which has a better catalytic effect on the hydrogenation reaction of isoparaffins. Further preferably, the metal active component is Pt or Pd, which can further improve the catalytic effect.
[0073] The method for loading the above active components on the nanorod-shaped ZSM-48 molecular sieve of the present application can be selected in the prior art, and the present application has no particular limitation. For example, the above hydroisomerization catalyst is obtained by impregnation, drying and calcination. In some preferred embodiments of the present application, when preparing the hydroisomerization catalyst, the drying temperature is 80-100°C, the drying time is 6-12h; the calcination temperature is 400-600°C, and the calcination time is 2-6h.
[0074] According to another typical embodiment of the present application, a use of the above hydroisomerization catalyst in alkane hydroisomerization reaction is provided. The above hydroisomerization catalyst significantly improves the selectivity of isoparaffin hydrogenation reaction and has high application value and prospects in the field of hydroisomerization dewaxing.
[0075] In some preferred embodiments of the present application, the temperature of the alkane hydroisomerization reaction is 240-360°C; the reaction pressure is 1-6 MPa; the volume ratio of hydrogen to alkane is 300-600; the mass space velocity is 0.5-12 h -1 , which can make the catalyst play a better role and further improve the selectivity and efficiency of the reaction.
[0076] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.
[0077] Example 1
[0078] At room temperature, the gel was prepared according to the following molar ratio: HMB:SiO2:Al2O3:H2O:NaOH=0.02:1:0.009:20:0.08, the seed crystal was ZSM-48 molecular sieve, and the addition amount was 2% of the mass of silica. First, 0.59g of sodium hydroxide was added to 40.33g of deionized water weighed in advance, and 1.328g of HMB (hexamethylammonium bromide) was added after stirring until the alkali source was dissolved, and 0.34g of sodium aluminate was added after stirring until the template was dissolved. After the aluminum source was completely dissolved and the mixed solution was relatively clear, 36.67g of silica gel was added dropwise, and after stirring evenly, 0.22g of ZSM-48 molecular sieve seed crystals were added, and continued to stir vigorously for 3 hours until the gel was formed.
[0079] (2) Crystallization process:
[0080] The gel was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in a rotary oven at 180°C, and dynamically crystallized at two temperatures at 40 RPM, first at 100°C for 24 hours, and then at 180°C for 24 hours.
[0081] (3) Post-processing process:
[0082] After the crystallization is completed, the reactor is cooled to room temperature, the reaction product is taken out, separated by conventional filtration or centrifugation, and washed with deionized water until the pH value of the supernatant is 7-8; the solid product is then transferred to a 100°C oven and dried for 8 hours, and then transferred to a muffle furnace and calcined at 550°C for 10 hours to remove the template; the product after removing the template is exchanged with 1 mol / L ammonium chloride solution at 80°C for 3 hours, and after cooling, the sample is taken out for filtration, washing, drying and calcination. The above process is repeated three times, and the mass content of the Na element is less than 1%, and the hydrogen-type ZSM-48 molecular sieve can be obtained.
[0083] The obtained samples were subjected to XRD test, and the test results were as follows: Figure 1 As shown, it can be seen that the sample has a typical ZSM-48 molecular sieve*MRE topological structure. All characteristic diffraction peaks are consistent with the diffraction peaks of ZSM-48 molecular sieves when compared with the standard spectrum. There is no impurity crystal peak and the crystallinity is good. The sample was tested by SEM, and the test results are as follows Figure 2 As shown, it has a rod-like crystal morphology, the crystal length is about 2-3 μm, and the particle size is uniform.
[0084] Example 2
[0085] At room temperature, the gel was prepared according to the following molar ratio: HMB:SiO2:Al2O3:H2O:NaOH=0.02:1:0.007:20:0.08, the seed crystal was ZSM-48 molecular sieve, and the addition amount was 2% of the mass of silica. First, 0.59g of sodium hydroxide was added to 40.33g of deionized water weighed in advance, and 1.328g of HMB (hexamethylammonium bromide) was added after stirring until the alkali source was dissolved, and 0.27g of sodium aluminate was added after stirring until the template was dissolved. After the aluminum source was completely dissolved and the mixed solution was relatively clear, 36.67g of silica gel was added dropwise, and after stirring evenly, 0.22g of ZSM-48 molecular sieve seed crystals were added, and continued to stir vigorously for 3 hours until the gel was formed.
[0086] (2) Crystallization process:
[0087] The gel was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in a rotary oven at 180°C, and dynamically crystallized at two temperatures at 40 RPM, first at 100°C for 24 hours, and then at 180°C for 24 hours.
[0088] (3) Post-processing process:
[0089] After the crystallization is completed, the reactor is cooled to room temperature, the reaction product is taken out, separated by conventional filtration or centrifugation, and washed with deionized water until the pH value of the supernatant is 7-8; the solid product is then transferred to a 100°C oven and dried for 8 hours, and then transferred to a muffle furnace and calcined at 550°C for 10 hours to remove the template; the product after removing the template is exchanged with 1 mol / L ammonium chloride solution at 80°C for 3 hours, and after cooling, the sample is taken out for filtration, washing, drying and calcination. The above process is repeated three times, and the mass content of the Na element is less than 1%, and the hydrogen-type ZSM-48 molecular sieve can be obtained.
[0090] The obtained samples were subjected to XRD test (see Figure 3 ) It can be seen that the sample has a typical ZSM-48 molecular sieve * MRE topological structure. All characteristic diffraction peaks are consistent with the diffraction peaks of ZSM-48 molecular sieves when compared with the standard spectrum. There is no impurity crystal peak and the crystallinity is good. The sample was tested by SEM (see Figure 4 ) showed that it had a rod-like crystal morphology, the crystal length was about 2-3 μm, the particle size was uniform, the particles were more complete and smooth, and there were no extra small fragments.
[0091] Example 3
[0092] At room temperature, the gel was prepared according to the following molar ratio: HMB:SiO2:Al2O3:H2O:NaOH=0.02:1:0.005:20:0.08, the seed crystal was ZSM-48 molecular sieve, and the addition amount was 2% of the mass of silica. First, 0.59g of sodium hydroxide was added to 40.33g of deionized water weighed in advance, and 1.328g of HMB (hexamethylammonium bromide) was added after stirring until the alkali source was dissolved, and 0.18g of sodium aluminate was added after stirring until the template was dissolved. After the aluminum source was completely dissolved and the mixed solution was relatively clear, 36.67g of silica gel was added dropwise, and after stirring evenly, 0.22g of ZSM-48 molecular sieve seed crystals were added, and continued to stir vigorously for 3 hours until the gel was formed.
[0093] (2) Crystallization process:
[0094] The gel was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in a rotary oven at 180°C, and dynamically crystallized at two temperatures at 40 RPM, first at 100°C for 24 hours, and then at 180°C for 24 hours.
[0095] (3) Post-processing process:
[0096] After the crystallization is completed, the reactor is cooled to room temperature, the reaction product is taken out, separated by conventional filtration or centrifugation, and washed with deionized water until the pH value of the supernatant is 7-8; the solid product is then transferred to a 100°C oven and dried for 8 hours, and then transferred to a muffle furnace and calcined at 550°C for 10 hours to remove the template; the product after removing the template is exchanged with 1 mol / L ammonium chloride solution at 80°C for 3 hours, and after cooling, the sample is taken out for filtration, washing, drying and calcination. The above process is repeated three times, and the mass content of the Na element is less than 1%, and the hydrogen-type ZSM-48 molecular sieve can be obtained.
[0097] The obtained samples were subjected to XRD test (see Figure 5 ) It can be seen that the sample has a typical ZSM-48 molecular sieve * MRE topological structure. All characteristic diffraction peaks are consistent with the diffraction peaks of ZSM-48 molecular sieves when compared with the standard spectrum. There is no impurity crystal peak and the crystallinity is good. The sample was tested by SEM (see Figure 6 ) showed that it has a rod-like crystal morphology, the crystal length is about 2-3μm, the particle size is uniform, and the surface is smoother.
[0098] Example 4
[0099] At room temperature, the gel was prepared according to the following molar ratio: HMB:SiO2:Al2O3:H2O:NaOH=0.02:1:0.004:20:0.08, the seed crystal was ZSM-48 molecular sieve, and the addition amount was 2% of the mass of silica. First, 0.59g of sodium hydroxide was added to 40.33g of deionized water weighed in advance, and 1.328g of HMB (hexamethylammonium bromide) was added after stirring until the alkali source was dissolved, and 0.14g of sodium aluminate was added after stirring until the template was dissolved. After the aluminum source was completely dissolved and the mixed solution was relatively clear, 36.67g of silica gel was added dropwise, and after stirring evenly, 0.22g of ZSM-48 molecular sieve seed crystals were added, and continued to stir vigorously for 3 hours until a gel was formed;
[0100] (2) Crystallization process:
[0101] The gel was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in a rotary oven at 180°C, and dynamically crystallized at two temperatures at 40 RPM, first at 100°C for 24 hours, and then at 180°C for 24 hours.
[0102] (3) Post-processing process:
[0103] After the crystallization is completed, the reactor is cooled to room temperature, the reaction product is taken out, separated by conventional filtration or centrifugation, and washed with deionized water until the pH value of the supernatant is 7-8; the solid product is then transferred to a 100°C oven and dried for 8 hours, and then transferred to a muffle furnace and calcined at 550°C for 10 hours to remove the template; the product after removing the template is exchanged with 1 mol / L ammonium chloride solution at 80°C for 3 hours, and after cooling, the sample is taken out for filtration, washing, drying and calcination. The above process is repeated three times, and the mass content of the Na element is less than 1%, and the hydrogen-type ZSM-48 molecular sieve can be obtained.
[0104] The obtained samples were subjected to XRD test (see Figure 7 ) It can be seen that the sample has a typical ZSM-48 molecular sieve * MRE topological structure. All characteristic diffraction peaks are consistent with the diffraction peaks of ZSM-48 molecular sieves when compared with the standard spectrum. There is no impurity crystal peak and the crystallinity is good. The sample was tested by SEM (see Figure 8 ) showed that it had a rod-like crystal morphology, the crystal length was about 2-3 μm, and the particle size was uniform.
[0105] Example 5
[0106] The difference from Example 1 is that the rotation speed during the crystallization process in step (2) is 100 RPM.
[0107] The obtained samples were subjected to XRD test (see Fig. 9 ) It can be seen that the sample has characteristic diffraction peaks of ZSM-48 molecular sieve, but there are other impurity crystal peaks and the crystallinity is poor.
[0108] Example 6
[0109] The difference from Example 1 is that the rotation speed during the crystallization process in step (2) is 10 RPM.
[0110] The obtained samples were subjected to XRD test (see Fig.10 ) It can be seen that the sample has characteristic diffraction peaks of ZSM-48 molecular sieve, but there are other impurity crystal peaks and the crystallinity is poor.
[0111] Comparative Example 1
[0112] The difference from Example 1 is that no seed crystals are added in step (1).
[0113] The obtained samples were subjected to XRD test (see Fig.11 ) It can be seen that the characteristic diffraction peak of ZSM-48 molecular sieve of the sample is not obvious; SEM test of the sample (see Fig.12 ) shows that it is composed of needle-shaped, needle-aggregated bundle-shaped crystal morphology and amorphous silicon aluminum. It can be seen that the growth of ZSM-48 molecular sieve crystals is not conducive to the addition of seed crystals.
[0114] Comparative Example 2
[0115] The difference from Example 1 is that the crystallization process in step (2) is as follows: the gel is transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in a rotary oven at 180° C., and crystallized at a rotation speed of 40 rpm / min for 36 hours.
[0116] The obtained samples were tested by XRD, and the results were as follows: Fig.13 , the sample was subjected to SEM test (see Fig.14 ) shows that an obvious bundle-like morphology is formed.
[0117] Comparative Example 3
[0118] (1) Preparation of hydrothermal system:
[0119] At room temperature, the gel was prepared according to the following molar ratio: HMB:SiO2:Al2O3:H2O:NaOH=0.02:1:0.014:20:0.12, the seed crystal was ZSM-48 molecular sieve, and the addition amount was 2% of the mass of silica. First, 0.88g of sodium hydroxide was added to 40.33g of deionized water weighed in advance, and 1.328g of HMB (hexamethylammonium bromide) was added after stirring until the alkali source was dissolved, and 0.54g of sodium aluminate was added after stirring until the template agent was dissolved, and after the aluminum source was completely dissolved and the mixed solution was relatively clear, 36.67g of silica gel was added dropwise, and after stirring evenly, 0.22g of ZSM-48 molecular sieve seed crystals (SiO2 / Al2O3 was 71) were added, and continued to stir vigorously for 3 hours until the gel was formed.
[0120] (2) Crystallization process:
[0121] The gel was transferred to a stainless steel reactor lined with polytetrafluoroethylene, placed in a rotary oven at 180°C, and dynamically crystallized at two temperatures at 40 RPM, first at 100°C for 24 hours, and then at 180°C for 24 hours.
[0122] (3) Post-processing process:
[0123] After the crystallization is completed, the reactor is cooled to room temperature, the reaction product is taken out, separated by conventional filtration or centrifugation, and washed with deionized water until the pH value of the supernatant is 7-8; the solid product is then transferred to a 100°C oven and dried for 8 hours, and then transferred to a muffle furnace and calcined at 550°C for 10 hours to remove the template; the product after removing the template is exchanged with 1 mol / L ammonium chloride solution at 80°C for 3 hours, and after cooling, the sample is taken out for filtration, washing, drying and calcination. The above process is repeated three times, and the mass content of the Na element is less than 1%, and the hydrogen-type ZSM-48 molecular sieve can be obtained.
[0124] The obtained samples were subjected to XRD test, and the test results were as follows: Fig.15 As shown, it can be seen that the sample has a typical ZSM-48 molecular sieve*MRE topological structure. All characteristic diffraction peaks are consistent with the diffraction peaks of ZSM-48 molecular sieves when compared with the standard spectrum. There is no impurity crystal peak and the crystallinity is good. The sample was tested by SEM, and the test results are as follows Fig.16 As shown, it has a needle-like crystal morphology, the crystal length is about 400-800nm, and the particle size is uniform. It can be seen that when the alkalinity is too high, it is difficult to generate a rod-shaped ZSM-48 molecular sieve.
[0125] Application Examples
[0126] The ZSM-48 molecular sieve synthesized in Example 1 was used as a carrier to load active metals to prepare a hydroisomerization catalyst for alkane hydroisomerization reaction. At the same time, ZSM-22 molecular sieve (Si / Al ratio 35) was used as a carrier and a hydroisomerization catalyst was prepared in the same way for comparison.
[0127] The preparation method of the hydroisomerization catalyst is as follows: the above carrier is loaded with 0.5 wt% of Pt catalyst by an impregnation method.
[0128] The conditions of the hydroisomerization reaction are as follows: temperature 573K, pressure 2.0MPa, hydrogen / hydrocarbon volume ratio 400. 1.2g of catalyst is loaded, and n-dodecane is used as the probe molecule, that is, n-dodecane is used as the reaction raw material.
[0129] When different hydroisomerization catalyst supports are selected and under different space velocity conditions, the conversion rate of n-dodecane and the selectivity of iso-dodecane are shown in Table 1.
[0130] Table 1
[0131] Hydroisomerization catalyst support <![CDATA[Air speed / h -1 > n-Dodecane conversion, wt% Isodecane selectivity, wt% ZSM-48 (Example 1) 10 35 70 ZSM-48 (Example 1) 1 70 34 ZSM-22 11 38 11 ZSM-22 1.5 82 5
[0132] From the results in the above table, it can be seen that the isododecane selectivity of the ZSM-48 molecular sieve catalyst is significantly higher than that of the ZSM-22 molecular sieve at similar conversion rates, and as the conversion rate increases, the isododecane selectivity of the ZSM-48 molecular sieve catalyst increases by 36 percentage points, which is much higher than that of the ZSM-22 molecular sieve catalyst. It can be seen that the ZSM-48 molecular sieve synthesized by the present invention has good isomeric product selectivity.
[0133] From the above description, it can be seen that the above-mentioned embodiments of the present invention achieve the following technical effects: This application prepares a nanorod-shaped ZSM-48 molecular sieve with a large adjustable range of silicon-aluminum ratio through a two-stage crystallization reaction performed at a specific temperature, and the particle morphology is uniform and the crystallinity is high. In addition, the synthesis cycle of the synthesis method of the present application is significantly shortened, and the raw materials are cheap and easy to obtain. Compared with other one-dimensional pore zeolites, the nanorod-shaped ZSM-48 molecular sieve prepared in this application exhibits more effective hydroisomerization performance, and the selectivity of isoparaffins is significantly improved, and it has a high application value and prospect in the field of hydroisomerization dewaxing.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for synthesizing nanorod-shaped ZSM-48 molecular sieve, characterized in that: include: Step S1, after uniformly mixing an alkali source, a template, an aluminum source, water and a silicon source, adding seed crystals for aging to obtain a gel; the molar ratio of the hydroxide in the alkali source to the silicon element in the silicon source is (0.01-0.09):1; Step S2, subjecting the gel to a first stage crystallization at 90-110° C. to obtain a first stage crystallization product; Step S3, subjecting the first stage product to second stage crystallization at 160-190° C., and subjecting the second stage crystallization product to post-treatment to obtain the nanorod-shaped ZSM-48 molecular sieve.
2. The method for synthesizing the nanorod-shaped ZSM-48 molecular sieve according to claim 1, characterized in that: The alkaline source is one or more of potassium hydroxide, sodium hydroxide and ammonia; The template agent is any one or more of pentamethamine bromide, hexamethamine bromide, hexamethamine hydroxide and 1,6-hexanediamine; The aluminum source is any one or more of pseudo-boehmite, sodium aluminate, and aluminum sulfate; The silicon source is any one or more of macroporous silica gel, silica gel or fumed silica; The seed crystal is a ZSM-48 molecular sieve. Preferably, the absolute value of the difference between the silicon-aluminum ratio of the ZSM-48 molecular sieve used as the seed crystal and the silicon-aluminum ratio of the feed is within 10%.
3. The method for synthesizing the nanorod-shaped ZSM-48 molecular sieve according to claim 1 or 2, characterized in that: The molar ratio of the silicon element in the silicon source to the aluminum element in the aluminum source is (25-250):1, preferably (30-140):1; The molar ratio of the template to the silicon element in the silicon source is (0.005-1.5):1, preferably (0.005-1.5):1; The molar amount of the water and the molar amount of the silicon element in the silicon source are (10-40):1, preferably (15-30):1; The amount of the seed crystal added is 1% to 6% of the mass of SiO2 in the silicon source.
4. The method for synthesizing nanorod-shaped ZSM-48 molecular sieve according to claim 1, characterized in that: The step S1 comprises: adding the alkali source, the template agent, and the aluminum source into deionized water, stirring until the mixture is uniform, obtaining a mixed solution, mixing the silicon source with the mixed solution uniformly, adding seed crystals for aging, and obtaining a gel; Preferably, the stirring speed is 300-600RPM.
5. The method for synthesizing nanorod-shaped ZSM-48 molecular sieve according to claim 1, characterized in that: The aging time is 0.5 to 3 hours, and the aging temperature is 20° C. to 35° C.
6. The method for synthesizing nanorod-shaped ZSM-48 molecular sieve according to claim 1, characterized in that: The first stage crystallization and the second stage crystallization are carried out under stirring conditions. Preferably, the stirring speeds of the first stage crystallization and the second stage crystallization are independently 30 to 50 RPM. The crystallization time is 6 to 24 hours; The time of the second stage crystallization is 12 to 24 hours.
7. The method for synthesizing nanorod-shaped ZSM-48 molecular sieve according to claim 1, characterized in that: The post-treatment includes washing, drying and roasting; The washing comprises washing the second-stage crystallization product with deionized water until the pH of the eluent is 7-8; The drying temperature is 60-120°C and the drying time is 8-12h; The calcination includes heating to 550-600°C at a rate of 2-4°C / min and maintaining for 6-12h; The post-treatment further comprises: subjecting the calcined product to ion exchange in a 0.5-2 mol / L ammonium chloride solution.
8. A nanorod-shaped ZSM-48 molecular sieve, characterized in that: The nanorod-shaped ZSM-48 molecular sieve is prepared by the synthesis method of any one of claims 1 to 7.
9. A hydroisomerization catalyst, characterized in that: It comprises a carrier and a metal active component, wherein the carrier is the nanorod-shaped ZSM-48 molecular sieve according to claim 8, and the metal active component comprises any one or more of Ni, Pt and Pd; Preferably, the weight of the metal active component is 0.05-1 wt % of the weight of the carrier.
10. Use of the hydroisomerization catalyst according to claim 9 in alkane hydroisomerization reaction; Preferably, the temperature of the alkane hydroisomerization reaction is 240-360°C; the reaction pressure is 1-6 MPa; the volume ratio of hydrogen to alkane is 300-600; the mass space velocity is 0.5-12 h -1 .
Citation Information
Patent Citations
Preparation method for ZSM-48 molecular sieve
CN102910642A
A hydroisomerization catalyst for nickel phosphorus supported on nano-ZSM-22 zeolite, its preparation method, and its application.
CN111013643B
ZSM-48 molecular sieve and preparation method and application thereof
CN110642266A
Long-chain n-alkane hydroisomerization catalyst and preparation method thereof
CN111135859A
Synthesis method and application of ZSM-48 molecular sieve with low silica-alumina ratio
CN114436289A
Cited By
Alkali metal salt induced nano ZSM-48 molecular sieve and preparation method thereof
CN122233397A